The Evaluatıon Of Frontal Cephalometrıc Graphıes Of Male Chıldren In Dıyarbakır Area - Jalan Devecioğlu Kama; Mine Akalar (Galenos Yayinevi, 1997)
In this study, Ricketts parameters were applied to frontal cephalometric radiographs of 100 male individuals (50 orphanage, 50 control). The measured values of individuals groupped according to growing periods was compared statiscally and an increase was observed in width of mandibula and face and also in height of nose with increasing of age in two groups.